PREPARATION OF ANION-EXCHANGE CELLULOSE FOR THE REMOVAL OF CHROMATE - Özgür Arar (Journal of the Chilean Chemical Society, 2019)
The quaternary ammonium group containing cellulose was prepared by the one-pot method and applied for the removal of chromate (CrO42-) ions from aqueous solution. The prepared sorbent was characterized by using elemental analyzer and Fourier transform infrared (FTIR) spectroscopy. Its ion exchange behavior toward CrO42- ions was investigated as a function of sorbent dose and initial solution pH. The kinetic and sorption equilibrium experiments were also carried out in a batch system. Equilibrium data were best fitted with the Langmuir model and the maximum ion exchange capacity of the sorbent was found as 3.8 mg of CrO42-/g sorbent.Moreover, the removal of CrO42- is achieved within 5 minutes. Furthermore, the calculated thermodynamic parameters disclosed that the ion exchange reaction is feasible, spontaneous and exothermic. In addition, the CrO4 2- ions can be desorbed from the sorbent by 1.0 M HCl solution with 95% regeneration efficiency.